MENATA KONSTITUSIONALITAS UNDANG-UNDANG MELALUI PENGUJIAN EX ANTE REVIEW SEBAGAI PERLINDUNGAN HAK KONSTITUSIONAL WARGA NEGARA - . Muslifah; Jadmiko Anom Husodo (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2024)
One effort to realize the protection and enforcement of human rights is through the establishment of statutory regulations. These laws and regulations must have objective value, follow all existing formation instruments and not conflict with higher provisions in order to achieve legal ideals and realize the protection of citizens' constitutional rights. However, the current fact is that the formation of laws often results in hyper-regulation, conflict between regulations, overlapping regulations, multiple interpretations, inconsistencies and the formation of regulations at high costs. Apart from that, quite a few laws produced by legislators are often deemed unconstitutional, resulting in judicial review by the Constitutional Court. The formation of regulations that are not in accordance with the constitution will certainly have a negative impact on the existence of the rule of law. Therefore, preventive efforts are needed, namely an ex ante review to test the draft law before it is finally passed and promulgated. The aim of this article is to examine the constitutionality of the draft law through ex ante review as a form of protecting the constitutional rights of citizens by establishing a new, independent institution. The method used in this research is a prescriptive doctrinal method with a statutory approach, comparative approach and conceptual approach. Data was obtained from books, journals, articles and analysis of statutory regulations. The results of this research indicate that ex ante review testing is an alternative to prevent violations of the constitutional rights of citizens because every draft law before it is passed and promulgated must be tested first by synchronizing it with the 1945 Constitution of the Republic of Indonesia and harmonizing it with other related laws so that there is no overlapping of laws and regulations so that the public is not worried about the laws that will be enforced.